Changes in adolescent intervertebral discs, end plates and bone marrow of lumbar spine in idiopathic thoracic scoliosis an mri based study - Kassim, Ahmad Fauzey (2010)
Intervertebral disc degeneration is known to occur as early as the first decade in normal individuals. In adolescent idiopathic thoracic scoliosis, the spinal curvature is thought to impart mechanical stresses on the lumbar spine. This in theory would lead to early degenerative discs changes, Modic changes and Schmorl’s nodes as part of the whole degenerative process. Before the advent of magnetic resonance imaging (MRI), proper assessment of the discs, end plates, vertebral bone marrow changes and Schmorl’s nodes were not possible. With the help of MRI, a more detailed and accurate assessment of the intervertebral disc and vertebral bone marrow is now possible. This was a cross sectional study with the aim to identify and grade lumbar intervertebral discs, end plates, bone marrow changes and Schmorl’s nodes in adolescent idiopathic thoracic scoliosis patients. Lumbar MRI films from 40 patients totaling 200 discs were recruited into this study during 6 month period. The patients’ ages were 15.5 ± 2.7 years old ( range 10 to 20). The Cobb’s angles average were 47.63° ± 14.1° (range 20° to 80°). The patients were those attending Spine clinic, Hospital Universiti Sains Malaysia and diagnosed with idiopathic thoracic scoliosis. MRI were ordered for them mainly due to complaints of back pain, neurological deficit and others. MRI films were obtained from the online database system and analyzed by a radiologist, looking for the changes mentioned before. Thoracic scoliosis Cobb’s angles were measured from patient’s AP(anteroposterior) radiological film of the spine. Demographic data regarding sex and age were obtained from the patients’ medical records. Our results showed that in adolescent idiopathic thoracic scoliosis patients, all lumbar discs were affected by degenerative changes mainly grade 2 and 3 in Pfirrmann classification system. No disc 6 was graded as normal (Pfirrmann 1). Modic changes(15%) and Schmorl’s nodes(5%) are not commonly found in the lumbar discs of idiopathic thoracic scoliosis. The severity of thoracic spinal curvature was not proven to affect grades (Pfirrmann) of degenerative disc changes, Modic changes and Schmorls nodes. (all p value >0.05) We concluded that lumbar discs in adolescent idiopathic scoliosis with a single thoracic curve are all affected by degenerative changes. The thoracic curvature was not proven to have a direct effect on the severity of disc changes, Modic changes and Schmorl’s nodes. Keyword: idiopathic scoliosis; intervertebral discs; Modic changes; Schmorl’s nodes; thoracic curvature